Sclerostin antibody treatment improves bone mass, bone strength, and bone defect regeneration in rats with type 2 diabetes mellitus. (15th February 2013) - Hamann, Christine; Rauner, Martina; Höhna, Yvonne; Bernhardt, Ricardo; Mettelsiefen, Jan; Goettsch, Claudia; Günther, Klaus‐Peter; Stolina, Marina; Han, Chun‐Ya; Asuncion, Franklin J; Ominsky, Michael S; Hofbauer, Lorenz C
Abstract: Type 2 diabetes mellitus results in increased risk of fracture and delayed fracture healing. ZDF fa/fa rats are an established model of type 2 diabetes mellitus with low bone mass and delayed bone healing. We tested whether a sclerostin‐neutralizing antibody (Scl‐AbVI) would reverse the skeletal deficits of diabetic ZDF rats. Femoral defects of 3 mm were created in 11‐week‐old diabetic ZDF fa/fa and nondiabetic ZDF +/+ rats and stabilized by an internal plate. Saline or 25 mg/kg Scl‐AbVI was administered subcutaneously (s.c.) twice weekly for 12 weeks ( n  = 9–10/group). Bone mass and strength were assessed using pQCT, micro–computed tomography (µCT), and biomechanical testing. Bone histomorphometry was used to assess bone formation, and the filling of the bone defect was analyzed by µCT. Diabetic rats displayed lower spinal and femoral bone mass compared to nondiabetic rats, and Scl‐AbVI treatment significantly enhanced bone mass of the femur and the spine of diabetic rats ( p  < 0.0001). Scl‐AbVI also reversed the deficit in bone strength in the diabetic rats, with 65% and 89% increases in maximum load at the femoral shaft and neck, respectively ( p  < 0.0001). The lower bone mass in diabetic rats was associated with a 65% decrease in vertebral bone formation rate, which Scl‐AbVI increased by sixfold, consistent with a pronounced anabolic effect. Nondiabetic rats filled 57% of the femoral defect, whereas diabetic rats filled only 21% ( p  < 0.05). Scl‐AbVI treatment increased defect regeneration by 47% and 74%, respectively ( p  < 0.05). Sclerostin antibody treatment reverses the adverse effects of type 2 diabetes mellitus on bone mass and strength, and improves bone defect regeneration in rats. © 2013 American Society for Bone and Mineral Research.